Association between maternal smoking and survival among infants with trisomy 21. Issue 7 (24th February 2022) - Ludorf, Katherine L.; Benjamin, Renata H.; Malik, Sadia; Langlois, Peter H.; Canfield, Mark A.; Agopian, A. J.
Abstract: Background: Trisomy 21 (T21) is common, with affected infants having an increased risk of infant mortality (5.9‐7.1%). Maternal smoking is associated with infant mortality in the general population, and we evaluated if similar associations were present among infants with T21. Methods: We identified infants with T21 from the Texas Birth Defects Registry, and maternal smoking and infant vital status were obtained from linked birth and death certificate data, respectively. Cox proportional hazards regression models were used to calculate hazard ratios between maternal smoking and death between 0 to ≤ 364 days, 28‐364 days, and 0‐27 days. Results: We found a significant association between maternal smoking and death between 0 to ≤ 364 (unadjusted HR 1.72, 95% CI 1.07, 2.77), which was no longer statistically significant after adjustment for covariates (adjusted HR 1.55, 95% CI 0.94, 2.56). A similar pattern was observed for death between 28‐364 days (adjusted HR: 1.68, 95% CI 0.93, 3.03), whereas the association for 0‐27 days (adjusted HR: 1.30, 95% CI 0.51, 3.29) was not statistically significant before and after adjustment. Conclusions: The observed magnitudes of associations were similar to previous estimates among the general population. Further work considering the role of other maternal and infant risk factors and social determinants of health is necessary to better understand the observed results.